Icnologia de depósitos marinhos rasos regressivos: um exemplo do permiano superior da Bacia do Paraná - Lima, João Henrique Dobler (Universidade do Vale do Rio dos Sinos, 2010)
This study analyzes and characterizes the paleoichnology of the Teresina Formation sedimentary rocks cropping out in Cerro Caveiras (Dom Pedrito, Rio Grande do Sul State, south of Brazil), aiming to refine the existing paleoecological and paleoenvironmental interpretations. The ichnofauna is composed of Bergaueria isp., Cochlichnus anguineus, Cruziana problematica, Diplocraterion isp., Diplopodichnus biformis, Helminthopsis isp., Lockeia siliquaria, Multina minima, Palaeophycus striatus, Palaeophycus tubularis, Planolites beverleyensis, Planolites montanus, Scolicia cf. plana, Teichichnus isp. and Thalassinoides isp., distributed in two main trace fossil suites, a brackish-water suite and a freshwater suite. Five sedimentary facies were described: (i) laminated or massive shale; (ii) fine-grained sandstone with climbing ripples; (iii) heterolithic deposits; (iv) trough crossstratified sandstone; and (v) hummocky and swalley cross-stratified sandstone. Wavegenerated structures predominates and facies associations suggest deposition in lower shoreface/offshore transition setting. Current-generated structures are also common. The recurrent replacement of brakish-water suite by freshwater suite and the maintenance of the last one for more time in the sedimentary succession suggest a significative input of freshwater into the marine zones. This pattern, and the fact that freshwater suite settlement always occur after the current-generated sandstone deposition suggest deltaic influence in the lower shoreface, in a restricted shallow sea context. Two stratigraphic surfaces should be inferred by trace fossil analysis: a co-planar surface (S1), composed of a regressive erosion surface and a transgressive surface, at least, and a flooding surface (S2), which marks the deepest and saltiest episode in the depositional system at the study area. The integrated analysis involving the ichnology and sedimentology of the Cerro Caveiras succession suggest that it possibly represents a distal expression of wave-dominated delta fronts.
Keywords: Icnofósseis; Formação teresina; Rio Grande do Sul; Assinaturas icnológicas; Paleoambiente; Paleoecologia; Trace fossils; Teresina formation; Rio Grande do Sul state; Ichnological signatures; Paleoenvironment; Paleoecology; ACCNPQ::Ciências Exatas e da Terra::Geologia